Effect of personalized moderate exercise training on Wistar rats fed with a fructose enriched water - Dupas, Julie (Nutr Metab (Lond), 2018)
BACKGROUND: Metabolic Syndrom has become a public health problem. It mainly results from the increased consumption of fat and sugar. In this context, the benefits of personalized moderate exercise training were investigated on a metabolic syndrome male wistar rat model food with fructose drinking water (20–25% w/v). Different markers including body weight, metabolic measurements, blood biochemistry related to metabolic syndrome complications have been evaluated. METHODS: Male Wistar rats were randomly allocated to 4 groups: control (sedentary (C, n = 8) and exercise trained (Ex, n = 8)), fructose fed (sedentary (FF, n = 8) and exercise trained fructose fed rats (ExFF, n = 10)). ExFF and Ex rats were trained at moderate intensity during the last 6 weeks of the 12 weeks-long protocol of fructose enriched water. Metabolic control was determined by measuring body weight, fasting blood glucose, HOMA 2-IR, HIRI, MISI, leptin, adiponectin, triglyceridemia and hepatic dysfunction. RESULTS: After 12 weeks of fructose enriched diet, rats displayed on elevated fasting glycaemia and insulin resistance. A reduced food intake, as well as increased body weight, total calorie intake and heart weight were also observed in FF group. Concerning biochemical markers, theoretical creatinine clearance, TG levels and ASAT/ALAT ratio were also affected, without hepatic steatosis. Six weeks of 300 min/week of moderate exercise training have significantly improved overweight, fasting glycaemia, HOMA 2-IR, MISI without modify HIRI. Exercise also decreased the plasma levels of leptin, adiponectin and the ratio leptin/adiponectin. Regarding liver function and dyslipidemia, the results were less clear as the effects of exercise and fructose-enriched water interact together, and, sometimes counteract each other. CONCLUSION: Our results indicated that positive health effects were achieved through a personalized moderate training of 300 min per week (1 h/day and 5 days/week) for 6 weeks. Therefore, regular practice of aerobic physical exercise is an essential triggering factor to attenuate MetS disorders induced by excessive fructose consumption.